Potassium intake during cell dehydration - Pereira, DTB; David, R. B.; Vendramini, R. C.; Menani, José Vanderlei [UNESP]; De Luca, L. A. (Elsevier B.V., 2005)
Isotonic NaCl is ingested in addition to water by cell-dehydrated rats in two-bottle tests. The objective of the present work was to find out whether mineral intake in the cell-dehydrated rat is specific to NaCl in a five-bottle test. Adult male Sprague Dawley rats had distilled water and four mineral solutions at palatable concentrations (0.01 M KCl, 0.05 mM CaCl2, 0.15 M NaHCO3, 0.15 M NaCl) simultaneously available for consumption. Cell-debydration was produced infusing 1.5 ml of NaCl solution (0.15, 0.25, 0.5, 1.01, 2.0, 4.0 M) intravenously for 10 min and intakes were recorded for the next hour. It was observed a NaCl concentration-dependent increase in 0.01 M KCl intake. The ingestion of the other mineral solutions was not significantly altered compared to infusion of 0.15 M NaCl. The ingestion of KCl was not related to changes in serum potassium concentration. The ingestion of KCl was reduced in half and water was the preferred fluid when the five-bottle test was performed with mineral solutions at isomolar (0.15 M) concentrations. There was no increase in intake of other mineral solution in the isomolar test. No preference was observed for palatable or isomolar solutions during early extracellular dehydration until 4 h after subcutaneous injection of furosemide, in spite of the increase in total volume intake. Therefore, mineral intake induced by cell dehydration is not specific for NaCl solution. The type of mineral solution available influences the choice and KCl. is the preferred solution of the cell-dehydrated rat in the conditions of the present study. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: thirst; preference; taste; sodium appetite; osmoreceptor; kaliuresis; potassium excretion; natriuresis; hypematremia; five-bottle test; two-bottle test; mineral intake